2018
DOI: 10.1056/nejmoa1801562
|View full text |Cite
|
Sign up to set email alerts
|

MUC5B Promoter Variant and Rheumatoid Arthritis with Interstitial Lung Disease

Abstract: BACKGROUND Given the phenotypic similarities between rheumatoid arthritis (RA)–associated interstitial lung disease (ILD) (hereafter, RA-ILD) and idiopathic pulmonary fibrosis, we hypothesized that the strongest risk factor for the development of idiopathic pulmonary fibrosis, the gain-of-function MUC5B promoter variant rs35705950, would also contribute to the risk of ILD among patients with RA. METHODS Using a discovery population and multiple validation populations, we tested the association of the MUC5B p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
263
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 390 publications
(327 citation statements)
references
References 41 publications
25
263
2
11
Order By: Relevance
“…We performed alternative analyses with adjustment for additional factors including medication use and RA severity factors, which produced similar results. There may be other unmeasured factors including biomarkers and a recently identified genetic risk factor in the MUC5B gene, the inclusion of which may have affected our results . We encourage continued collaborative studies to identify and validate additional risk factors for RA‐ILD, as well as to develop and test interventions that may reduce RA‐ILD susceptibility and improve outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…We performed alternative analyses with adjustment for additional factors including medication use and RA severity factors, which produced similar results. There may be other unmeasured factors including biomarkers and a recently identified genetic risk factor in the MUC5B gene, the inclusion of which may have affected our results . We encourage continued collaborative studies to identify and validate additional risk factors for RA‐ILD, as well as to develop and test interventions that may reduce RA‐ILD susceptibility and improve outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The single greatest risk factor, genetic or otherwise, for the development of IPF and RA‐ILD is a gain of function, single nucleotide polymorphism (SNP) in the promoter region of the MUC5B gene (promoter variant rs35705950) . The wild‐type guanine (G) is switched for the thymidine (T) nucleotide (risk allele).…”
Section: Disease Associationsmentioning
confidence: 99%
“…The single greatest risk factor, genetic or otherwise, for the development of IPF and RA-ILD is a gain of function, single nucleotide polymorphism (SNP) in the promoter region of the MUC5B gene (promoter variant rs35705950). 52,53 The wild-type guanine (G) is switched for the thymidine (T) nucleotide (risk allele). This variant has a dose-dependent effect, with those individuals heterozygous for the risk allele (GT) 4.5 times more likely to develop the disease, increasing to twenty times more likely if homozygous for the risk allele (TT).…”
Section: Mucins In Pulmonary Fibrosismentioning
confidence: 99%
“…While several studies have suggested a relationship between the genetic factor the shared epitope and ILD in RA, that relationship may be confounded by other associations between the shared epitope, smoking (another risk factor for lung disease), and autoantibody positivity in RA . More recently, a genetic gain‐of‐function polymorphism in the MUC5B promoter variant, which has been previously associated with idiopathic pulmonary fibrosis (IPF), has also been associated with RA‐ILD, and in particular with UIP which is the form of ILD most similar to the form seen in IPF . Of note, while this polymorphism is associated with an increase in MUC5B expression and mucociliary dysfunction in the distal airway, it has not yet been associated with AD in RA; however, its possible influence on airway inflammation and immunity raises the possibility of a relationship between AD and ILD in RA, as will be discussed further below.…”
Section: Risk Factors For Ra‐related Lung Diseasementioning
confidence: 99%